Tinjauan Yuridis Normatif Atas Perlindungan Hukum Bagi Pasien Sebagai Konsumen Dalam Malpraktek Di Rumah Sakit - Fauji Salim (Universitas Islam Indonesia, 2020)
Medical malpractice occurs when doctors make mistakes in fulfilling their obligations, namely providing medical services to patients, which causes civilian losses. This is often accompanied by consequences that become the elements of certain criminal acts. Therefore, this study aims to answer two problems: First, what is the normative juridical review of consumer protection for patients in hospitals? Second, how is consumer protection for patients in the event of malpractice in the hospital? This is a normative juridical research with a statutory approach, this study concludes that the purpose of running a hospital according to the Hospital Law is to provide legal certainty to patients, society and human resources, so the hospital plays an important role in monitoring every doctor's activity in carrying out his profession. so that there is no negligence that could harm the patient and the doctor himself; Meanwhile, legal protection and health services include administrative, civil and criminal aspects.